2021
DOI: 10.1111/bjep.12458
|View full text |Cite
|
Sign up to set email alerts
|

Cultural diversity approaches in schools and adolescents’ willingness to support refugee youth

Abstract: Background Culturally diverse schools contribute to adolescents’ intergroup relations. Complex and inclusive social identities are mechanisms that can explain the link between structural school cultural diversity (i.e., proportion of students of immigrant descent and the number of different ethnic groups) and positive intergroup relations. We expected that similar mechanisms might be at play linking cultural diversity approaches in schools with adolescents’ intergroup relations. Aim We examined the link betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 80 publications
1
10
0
Order By: Relevance
“…An additional limitation of the present study stems from focusing on only one interpersonal facet of the cultural pluralism approach (i.e., perceived interest of teachers in children's cultural background). However, endorsement of such an approach also implies learning about intercultural relationships and multicultural topics (Aral et al, 2021 ; Schachner et al, 2016 ). Future studies considering such additional aspects of cultural pluralism (or more inclusive polyculturalism; Schachner et al, 2021 ) would make it possible to explore further the possible effects of multiple cultural affiliations on positive and negative contact.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional limitation of the present study stems from focusing on only one interpersonal facet of the cultural pluralism approach (i.e., perceived interest of teachers in children's cultural background). However, endorsement of such an approach also implies learning about intercultural relationships and multicultural topics (Aral et al, 2021 ; Schachner et al, 2016 ). Future studies considering such additional aspects of cultural pluralism (or more inclusive polyculturalism; Schachner et al, 2021 ) would make it possible to explore further the possible effects of multiple cultural affiliations on positive and negative contact.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the possible moderating effect of group membership (whether belonging to an ethnic minority or a majority group) on the association between cultural diversity approaches and intergroup outcomes is still largely unclear (e.g., Aral et al, 2021 ; Schwarzenthal et al, 2018 ), teachers' handling of cultural diversity in a constructive way might be equally beneficial for both groups. Such expectations stand to reason, especially when the characteristics of ethnic minority adolescents in Italy (e.g., mainly second‐generation youth of European descent; Ministero dell'Istruzione—Ufficio Statistica e Studi, 2021 ) are taken into account.…”
Section: The Present Studymentioning
confidence: 99%
“…Examining this question in Germany, in particular, is important given the high number of refugee youth in Germany (Eurostat, 2021). Further, prior research on German adolescents' attitudes toward refugees documents that more German adolescents perceived that they learned about the cultural history and traditions of both Germans and refugees and the similar German adolescents saw themselves and refugees, the more prosocial they intended to be toward refugees (Aral et al, 2021). Additionally, prior research demonstrates that German adolescents were more likely to include Syrian refugees who had good German language skills, suggesting the importance of cultural integration for inclusivity (Beißert et al, 2020).…”
Section: The Special Situation Of Refugee Youthmentioning
confidence: 99%
“…According to surveys and interviews, 6- to 11-year-olds in Germany are familiar with refugees and most have met refugee children in school, playgrounds, or during after school activities [ 24 ]. Moreover, recent studies have found that adolescents show more inclusive behavioural tendencies towards Syrian refugee peers with good German language skills than to those with bad German skills [ 26 ] and that cultural diversity in school settings promotes prosocial intentions towards refugee youth [ 25 ]. Relatedly, a study with 9- to 12-year-olds in the Netherlands showed that perceived similarity between Dutch and refugee children correlated with positive intergroup attitudes towards refugee children [ 65 ].…”
Section: Introductionmentioning
confidence: 99%
“…Increasingly, researchers have stressed the need to extend studies of intergroup attitudes beyond minimal group settings and to include macro-contextual variables such as historic and geographic factors [18][19][20]. To date, most research in the context of the so-called refugee crises in Germany has focused on newly arrived refugee children and youth themselves [21][22][23] and on social relations between and intergroup attitudes of refugee youth and host society youth [24][25][26]. However, very few studies have focused on young children's perceptions of and attitudes towards refugee peers in this unique historical context in Germany [24].…”
Section: Introductionmentioning
confidence: 99%